Hearing things : the work of sound in literature - Leighton, Angela, 1954- (The Belknap Press of Harvard University Press, 2018)
Hearing Things is a meditation on sound's work in literature. Drawing on the writings of critics and philosophers but especially on the comments of many poets and novelists who have pointed to the role of the ear in writing and reading, it offers a reconsideration of literature itself as an exercise in hearing things. Ranging from Alfred Tennyson to Alice Oswald, Virginia Woolf to Marilynne Robinson, Walter de la Mare to Les Murray, Angela Leighton examines various ways of listening to the printed word, while examining how writers themselves manage the expressivity of sound in their silent writings. Although her focus is on poets from the nineteenth to the twenty-first centuries--Alfred Tennyson, W.B. Yeats, Walter de la Mare, Robert Frost, Wallace Stevens, Elizabeth Bishop, Les Murray, Jorie Graham, and Anne Stevenson--Leighton expands her scope to include letter writing, rhythm, and the difficult relationship between philosophical and literary texts. While her larger argument is always answerable to the specifics of the writer under discussion, one clear message emerges from the whole: literature by its very nature commands listening, and listening is a form of cognitive attention that has often been overlooked.--